Study on Spatio-Temporal Variation of Runoff in Flood Season in Hanjiang River Basin - WANG Dong; WU Dongdong; XIE Xiaobai; LI Xuehui (Renmin Zhujiang, 2020)
Based on the average daily flow data of five typical hydrologic stations from 1956 to2016 in the Hanjiang River Basin, this paper analyzes the spatio-temporal vibrationcharacteristics of runoff in flood season by means of mathematical statistics, establishes the VICmodel applicable to Hanjiang River Basin according to the hydrometeorological data, DEM, soil typeand vegetation cover data, and analyzes the spatial distribution characteristics of runoff inflood season based on runoff simulation results of the VIC model. The results show that: therunoff of the five stations in flood season showed a downward trend, and there were strongchanges around 1990 with periodic oscillation characteristics of 6~8 years and 18~21 years;According to the calibration and validation results of the model, with good simulation accuracy,the VIC model can basically reflect the rainfall and runoff characteristics of the Hanjiang RiverBasin; Based on the change point in 1990, the difference on spatial distribution of runoff insummer flood season is larger, and the extremum center was transferred to a certain extent. Theextremum in autumn flood season and flood season with deep runoff was decreasing, and thevariation of extremum center was smaller. The results could be considered as a reference forunderstanding the variation of flood resources, rain-flood resources utilization and optimalallocation of water resources in Hanjiang River Basin.